2021
DOI: 10.3390/children8050389
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Father–Child Play Interactions and the Impacts on Child Development

Abstract: Father–child play engagement has been linked to a variety of child developmental outcomes. However, the most prevalent types of play and child developmental outcomes utilised in research remains unclear. The aim of this study was to systematically review the literature on father–child play interactions and the association with child developmental outcomes for children aged 0–10 years. Database searches generated 1622 abstracts that matched the specified search criteria. Abstract screening and full-text review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 69 publications
(93 reference statements)
2
26
0
1
Order By: Relevance
“…This may have implications for a child’s development if highly frequent RTP is of a low quality, whereby the father dominates the game and shows little warmth or positive regard towards their child. A systematic review exploring the developmental impacts of dyadic father–child play demonstrated that a father’s negative affect towards their child during play predicted poorer social and behavioural outcomes for children, such as lower sharing, peer ratings, and social acceptance [ 49 ]. Furthermore, negative effects have also been found for play interactions, whereby fathers, who frequently engage in RTP, are submissive and allow their child to dominate the play.…”
Section: Discussionmentioning
confidence: 99%
“…This may have implications for a child’s development if highly frequent RTP is of a low quality, whereby the father dominates the game and shows little warmth or positive regard towards their child. A systematic review exploring the developmental impacts of dyadic father–child play demonstrated that a father’s negative affect towards their child during play predicted poorer social and behavioural outcomes for children, such as lower sharing, peer ratings, and social acceptance [ 49 ]. Furthermore, negative effects have also been found for play interactions, whereby fathers, who frequently engage in RTP, are submissive and allow their child to dominate the play.…”
Section: Discussionmentioning
confidence: 99%
“…Attention-oriented interventions employed before the child sets foot in a classroom could therefore set them up for success in the classroom and beyond. One example from the developmental literature is the finding that regularly engaging in various types of play activities with a young child can produce a wide array of social, behavioral, and cognitive benefits (e.g., Robinson et al, 2021). Of specific interest is cooperative play-fighting in the form of structured rough-and-tumble play, which is energetic body-contact play observed in many mammalian species and hypothesized to be an important feature of parent-child relationships to facilitate bonding and help form a secure attachment (e.g., Fletcher et al, 2013;Paquette, 2004;StGeorge et al, 2021).…”
Section: Improving Attention Prior To School Enrollmentmentioning
confidence: 99%
“…As play becomes increasingly dramatic and abstract, the highest stages of socialization and cognition begin to develop, culminating in enhanced self-regulatory behavior such as attention control. Some studies have indeed shown that engagement in rough-and-tumble play has positive cognitive and behavioral outcomes in animals (e.g., Bell et al, 2009;Dallaire & Mason, 2017) and humans (e.g., Robinson et al, 2021), including being associated with increased self-regulatory functioning and attention control (e.g., Anderson et al, 2019;StGeorge and Freeman. 2017; also see Panksepp, 2008).…”
Section: Improving Attention Prior To School Enrollmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review suggests that due to the complexity of dyadic interactions, paternal behaviour can have vastly different associations, both positive and negative outcomes on child development [ 5 ]. Stimulating play also enhances the adaptability of a child to a chronic somatic condition such as cystic fibrosis, congenital heart defects, and promotes cognitive, social, emotional, and psychomotor functioning, who otherwise will have a significantly increased risk for physical, social, emotional, and cognitive problems later in life [ 6 ].…”
Section: Introductionmentioning
confidence: 99%